Effectiveness of Human Resource Practices among Printing Press Organizations in Sivakasi - Raman R, Kasi; N, Manikandan (International Journal of Scientific Research and Management (IJSRM), 2021)
The research was entitled as “Effectiveness of Human Resource Practices among Printing Press Organizations in Sivakasi”, reveals the importance of existing human resource practices followed in the organizations. The study analyses the various areas of human resource management in the organization such as recruitment and selection, training and development, performance appraisal, compensation policy and remuneration, motivation and welfare measures, and Industrial relations. The study examines the application of Human resource practices within the areas of the organization. The study confronts the functions and role of HR executives in focus with recruitment and selection of manpower and also training & development for the workforce. The research methodology was carried out in a survey cross-sectional applied to 350 respondents. Result of research showed that negative correlation between the performance appraisal and compensation. The findings revealed that the Human resource practices are the most important indicators in determining the growth of Printing Press organizations in Sivakasi.